Membangun Budaya Organisasi Sebagai Upaya Peningkatan Kinerja - Diawati, Elly; Kahir, Abd. (Institut Riset dan Pengembangan Indonesia, 2023)
Organizational Culture has an important role in determining the growth of the organization. Organizations can grow and develop because the organizational culture contained in them is able to stimulate the morale of the human resources in it so that organizational performance increases. For employees, organizational culture is interpreted as implementation guidelines and technical guidelines. This research was conducted at the Department of Population and Civil Registration of Sumenep Regency. Research on building organizational culture as an effort to improve performance is focused on seven characteristics of organizational culture, namely innovation and courage to take risks, attention to detail, result orientation, people orientation, team orientation, aggressiveness, and stability. The method used in this research is a qualitative research method in which all explanations regarding organizational culture in improving employee performance are described descriptively. Data and research results were obtained from observations, interviews with several informants and documentation. The results of the study show that organizational culture in the Department of Population and Civil Registration of Sumenep Regency can improve employee performance. Organizational culture in the Department of Population and Civil Registration of Sumenep Regency can be a driving force for performance and help improve work performance, because it is able to create motivation for employees to give their best abilities in taking advantage of the opportunities provided by the Office.